Beer in Czech Art - Jana ORLOVÁ (Sztuka i Dokumentacja)
The study offers, within its spatial limitations, a sketch of the complex relationship between Czechs and beer, beer and Czech art, and beer within Czech art. It shows that national alcoholism has deep roots that are directly linked to national self-identification – which in turn is linked to art. In the study, the author has used a short historical excursion to grasp the phenomenon also culturally and sociologically. The study is devoted to examples from visual arts, literature, and song lyrics. Through a selection of examples, the nature of Czech beer culture and art is portrayed in order to give the reader the most specific idea of the nature of this phenomenon.